Discovery of thienothiazolocarboxamide analogues as novel anti-tubercular agent. Issue 23 (1st December 2020) - Jin, Guanghai; Mi Kim, Young; Lee, Aram; Choi, Junghwan; Kang, Sunhee; Seo, Mooyoung; Jea Seo, Jeong; Lee, Sumi; Kang, Juhee; Kim, Jaeseung; Park, Sinyoung; Woo, Minjeong; et al.
Graphical abstract: Highlights: Thienothiazolocarboxamide analogues were prepared and evaluated as anti-tubercular agents. Compound 42 showed activities against M. tuberculosis H37Rv replicating outside and inside macrophages (extracellular IC50  = 0.76 μM, intracellular IC50  = 0.19 μM). Compound 42 showed favorable in vivo PK profile and efficacy in a murine model of tuberculosis which proposed it as a potential lead compound for further evaluation. Abstract: In order to identify anti-tubercular agents with a novel scaffold, commercial libraries of small organic compounds were screened against a fluorescent strain of Mycobacterium tuberculosis H37Rv, using a dual phenotypic assay. Compounds were assessed against bacteria replicating in broth medium, as well as inside macrophages, and thienothiazolocarboxamide (TTCA) scaffold was identified as hit in both assays, with submicromolar inhibitory concentrations. Derivatives of TTCA were further synthesized and evaluated for their inhibitory effects on M .  tuberculosis H37Rv. In the present study we report the structure–activity relationship of these TTCA derivatives. Compounds 28, 32 and 42 displayed good anti-tubercular activities, as well as favorable ADME and PK properties. Compound 42 exhibited excellent oral bioavailability in mice with high distribution to lungs, within 1 h. It was found to be efficacious in a dose dependent manner in a murine model of M. tuberculosis infection. Hence, compound 42 is now under evaluation as a potential lead candidate for treatment of tuberculosis.